PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI MOTIVASI KARYAWAN DI KANTOR KECAMATAN KALIKAJAR KABUPATEN WONOSOBO - Indry Mey Purwani; Theresia Pradiani; Mohammad Maskan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Law number 25 of 2009 is an activity conducted by public service providers to meet the needs of the residents in each region. This research aims to analyze the phenomenon related to the organizational culture of the Kalikajar Subdistrict Office, which appears too relaxed, with no deadlines and work briefings, causing employees to neglect their tasks. the physical work environment of the room, which is not spacious and well-organized, computers and printers that need updating because they are slow, and the non-physical environment such as the room temperature, which is quite hot, as well as some employee relationships that are not harmonious due to differences in perception and work methods. Both variables affect performance through motivation at the Kalikajar Subdistrict Office, Wonosobo Regency. The sampling technique used was saturated sampling, where the instrument taken included all employees at the Kalikajar Sub-district Office, Wonosobo Regency, totaling 32 employees. The data for this research were analyzed quantitatively using path analysis methods with validity and reliability tests, R-square, t-test, and f-test using the SPSS application. The research results show that: 1) organizational culture affects motivation, 2) work environment does not affect motivation, 3) organizational culture affects performance, 4) work environment does not affect performance, 5) motivation affects performance, 6) organizational culture and work environment simultaneously affect motivation, 7) organizational culture and work environment simultaneously affect performance, 8) organizational culture affects performance through motivation, 9) work environment does not affect performance through motivation, 10) motivation can moderate the effect of organizational culture on performance, accepted.